2017
DOI: 10.1016/j.physio.2016.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The quality of clinical practice guidelines for chronic respiratory diseases and the reliability of the AGREE II: an observational study

Abstract: The quality of evidence-based clinical practice guidelines for chronic respiratory diseases relevant to physiotherapy could be improved, particularly in consideration with applicability. The number of assessors for AGREE II could be reduced because of the good inter-rater reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…The domains with the lowest quality appraisal scores were ‘rigour of development’ with an average score of 50.21% and ‘applicability’ with an average score of 45.05%. These findings are consistent with previous studies’ findings [ 37 39 ]. There was agreement on only six guidelines to be recommended for use without modifications [ 18 , 19 , 21 , 27 , 29 , 35 ], while 11 guidelines were recommended for use in practice with modifications [ 12 – 15 , 20 , 23 , 24 , 26 , 30 , 31 , 34 ].…”
Section: Discussionsupporting
confidence: 94%
“…The domains with the lowest quality appraisal scores were ‘rigour of development’ with an average score of 50.21% and ‘applicability’ with an average score of 45.05%. These findings are consistent with previous studies’ findings [ 37 39 ]. There was agreement on only six guidelines to be recommended for use without modifications [ 18 , 19 , 21 , 27 , 29 , 35 ], while 11 guidelines were recommended for use in practice with modifications [ 12 – 15 , 20 , 23 , 24 , 26 , 30 , 31 , 34 ].…”
Section: Discussionsupporting
confidence: 94%
“…The overall assessment of conformity between reviewers across each domain was calculated using the intra-class correlation coefficient (ICC) with 95% CIs (14). ICC that was 0.75 or higher was interpreted as excellent reliability, 0.40 to 0.75 as moderate reliability and less than 0.40 as poor reliability (15)(16)(17). Descriptive and statistical analyses were conducted using SPSS version 23.0 (IBM Corporation).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, compared with other CPGs scored with the AGREE-II instrument, those published by the NCCN appear to have as good or stronger methodological quality 11 13–15. A recent evaluation in JAMA Internal Medicine of CPGs for the pharmacological management of non-communicable diseases in primary care found that three CPG characteristics are associated with high-quality CPGs: greater than 20 authors, development at a government institution and reported funding 16.…”
Section: Discussionmentioning
confidence: 99%